Interaction of Anticancer Drug Methotrexate with DS-DNA Analyzed by Spectroscopic and Electrochemical Methods - R. Hajian; M. Tavakol (E-Journal of Chemistry)
Cyclic voltammetry coupled with UV/Vis spectroscopic techniques were used to study the interaction of methotrexate (MTX), an antitumor drug, with double stranded fish sperm DNA (ds-DNA) in phosphate buffer solution (pH 7.4). The interaction of MTX with DNA could result a considerable decrease in the MTX peak current. The variations in the spectroscopy and electrochemical characteristics of MTX indicated MTX bind to DNA by a groove binding mode. This conclusion was reinforced by viscosity data. The apparent transfer coefficients (α) and the number of electron transferred (n) of methotrexate in the absence and preset of ds-DNA have determined using anodic Tafel plots of MTX and MTX-DNA adduct on the surface of glassy carbone electrode. The diffusion coefficients of MTX in the absence (D0)f and presence (D0)b of DNA were calculated as 7.30×10−6 and 3.40×10−6 Cm2 s−1 respectively. In spectrophotometric studies, the slopes of the calibration curves for methotrexate in the absence and presence of ds-DNA differ significantly. These studies are valuable for a better understanding the detailed mode of MTX-DNA interaction, which should be important in deeper insight into the therapeutic efficacy of MTX and design of new DNA targeted drug.